1999
DOI: 10.1161/01.cir.100.4.400
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase Inhibitor Prevents Acute Lung Injury After Cardiopulmonary Bypass

Abstract: Background-Acute lung injury (ALI) after cardiopulmonary bypass (CPB) results from sequential priming and activation of neutrophils. Activated neutrophils release neutral serine, elastase, and matrix metalloproteinases (MMPs) and oxygen radical species, which damage alveolar-capillary basement membranes and the extracellular matrix, resulting in an ALI clinically defined as adult respiratory distress syndrome (ARDS). We hypothesized that treatment with a potent MMP and elastase inhibitor, a chemically modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 27 publications
6
100
0
3
Order By: Relevance
“…During VILI, high airway pressures and volumes lead to cell stretch, causing epithelial damage and an inflammatory response within the lungs. Increased levels of MMPs have been documented in different models of acute lung injury (8,13,27) and in the special case of VILI (14,25). MMP-9 is one of the most studied MMPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During VILI, high airway pressures and volumes lead to cell stretch, causing epithelial damage and an inflammatory response within the lungs. Increased levels of MMPs have been documented in different models of acute lung injury (8,13,27) and in the special case of VILI (14,25). MMP-9 is one of the most studied MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these findings, it has been suggested that MMP-9 inhibition could be useful in models of sepsis (42), acute lung injury (8), and VILI (14,25) by decreasing the inflammatory response and tissue damage. However, nonselective inhibitors can modify the activity of other enzymes, precluding any firm conclusion on the specific role of MMP-9.…”
mentioning
confidence: 99%
“…Animals receiving CPB and LPS developed ARDS-like pathology with 60% survival. Clinical features of ARDS were prevented by CMT-3 treatment, with a 100% survival rate compared with 60% during the 270 min of experimentation [41]. It is also worth noting that all these animals were subject to tidal volumes of 12 mL?kg -1 during this experiment, which essentially provides another injurious stimulus to the lungs in all groups.…”
Section: Tetracyclinesmentioning
confidence: 95%
“…In a CPB pig model of lung injury, CMT-3 was used to assess the response to MMP inhibition [41]. 30 min after CPB was initiated, either low-dose LPS (1 mg?kg -1 ), a control or simultaneous LPS and CMT-3 were given.…”
Section: Tetracyclinesmentioning
confidence: 99%
“…In this issue of Circulation, Carney et al 18 have tested the hypothesis that increased metalloproteinase and elastase levels play a pathophysiological role in pulmonary microvascular injury in a porcine model of postpump syndrome. The authors used CPB plus endotoxin challenge to induce postpump-like syndrome on the basis of their previous experience showing that both a priming stimulus (CPB) and a secondary trigger (endotoxin) are necessary to create the syndrome in this model.…”
Section: See P 400mentioning
confidence: 99%